Insulin/insulin-like growth factor signaling pathway promotes higher fat storage in Drosophila females - Puja Biswas; Jennifer A. Bako; J. Beatrice Liston; Huaxu Yu; Lianna W. Wat; Colin J. Miller; Michael D. Gordon; Tao Huan; Molly Stanley; Elizabeth J. Rideout (Cell Reports, 2025)
Summary: In Drosophila, adult females store more fat than males. While the mechanisms that restrict body fat in males are becoming clearer, less is known about how females achieve higher fat storage. Here, we perform a detailed investigation of the mechanisms that promote higher fat storage in females. We show that a greater intake of dietary sugar supports higher fat storage due to female-biased remodeling of the fat body lipidome. Dietary sugar stimulates a female-specific increase in Drosophila insulin-like peptide 3 (Dilp3), which acts together with greater peripheral insulin sensitivity to augment insulin/insulin-like growth factor signaling pathway (IIS) activity in adult females. Indeed, Dilp3 overexpression prevented the female-biased decrease in body fat after removal of dietary sugar. Given that adult-specific IIS inhibition caused a female-biased decrease in body fat, our data reveal IIS as a key determinant of female fat storage.